2020
DOI: 10.1029/2020jd032918
|View full text |Cite
|
Sign up to set email alerts
|

Three Years of the Lightning Imaging Sensor Onboard the International Space Station: Expanded Global Coverage and Enhanced Applications

Abstract: The Lightning Imaging Sensor (LIS) was launched to the International Space Station (ISS) in February 2017, detecting optical signatures of lightning with storm‐scale horizontal resolution during both day and night. ISS LIS data are available beginning 1 March 2017. Millisecond timing allows detailed intercalibration and validation with other spaceborne and ground‐based lightning sensors. Initial comparisons with those other sensors suggest flash detection efficiency around 60% (diurnal variability of 51–75%), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
95
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 93 publications
(131 citation statements)
references
References 67 publications
9
95
0
Order By: Relevance
“…Note that all three systems show a lack of lightning data over the ocean to the west of South America. This lack of lightning has been seen in other studies with different lightning sensors, e.g., Albrecht et al (2016), Blakeslee et al (2020). To keep the DE and FAR statistics from having too much variation, we will not plot DE and FAR values when the number of flashes per grid point drops below 20 flashes for either the GLMs or the virtual ground truth source.…”
Section: Accepted Articlementioning
confidence: 93%
“…Note that all three systems show a lack of lightning data over the ocean to the west of South America. This lack of lightning has been seen in other studies with different lightning sensors, e.g., Albrecht et al (2016), Blakeslee et al (2020). To keep the DE and FAR statistics from having too much variation, we will not plot DE and FAR values when the number of flashes per grid point drops below 20 flashes for either the GLMs or the virtual ground truth source.…”
Section: Accepted Articlementioning
confidence: 93%
“…Pixelated lightning imagers including the Optical Transient Detector (OTD; Boccippio et al, 2000), Lightning Imaging Sensor (LIS; Blakeslee et al, 2020;Christian et al, 2000), Geostationary Lightning Mapper (GLM; Goodman et al, 2013;Rudlosky et al, 2018), and Lightning Mapping Imager (LMI; Yang et al, 2017) record the spatial distributions of optical energy that result from lightning pulses. These observed spatial radiance patterns often deviate from the simple idealized model of radiance decreasing only with radius from the center pixel.…”
Section: Introductionmentioning
confidence: 99%
“…There were 285 ISS LIS flashes matched to lightning identified from METEOR camera frames, which is a relative DE of 92%. Blakeslee et al [2020] observed that ISS LIS relative DE ranged from 51% to 75% when compared to other lightning observing systems, and the higher DE obtained here again is likely in part due to nighttime, the optical nature of METEOR, and the large average flash size during this period of time. individual frames (Fig.…”
Section: Flash Population Statistics Using Meteormentioning
confidence: 39%
“…Lightning Imaging Sensor (LIS) was launched and made operational on the International Space Station [ISS; Blakeslee and Koshak, 2016;Blakeslee et al, 2020]. This instrument has heritage back to the Tropical Rainfall Measurement Mission [TRMM; Kummerow et al, 1998] LIS [Christian et al, 2000;Boccippio et al, 2001] instrument, where ISS LIS was the spare backup in the event the LIS instrument on TRMM failed during preparation and launch.…”
Section: Accepted Articlementioning
confidence: 99%
See 1 more Smart Citation